Quality of Democracy in Des Sidodadi Ramunia Through Political Participation of New Voters in the 2024 General Election - Sihombing, Frans Togu; Julia Ivanna (Ampera: A Research Journal on Politics and Islamic Civilization, 2024)
Indonesian elections serve as a fundamental manifestation of democracy and a mechanism through which citizens assert their sovereignty over the state and government. The engagement of novice voters in Sidodadi Ramunia Village during the General Election offers a compelling area of study. New voters often exhibit distinct characteristics compared to older generations, such as being more critical, independent, and dissatisfied with the status quo, with a propensity for change. These traits are conducive to fostering a well-informed electorate, characterized by voters who make rational and considered choices. This study focuses on novice voters in Sidodadi Ramunia Village, who are anticipated to sustain their political engagement. Their continued participation in the democratic process is crucial for advancing Indonesia's democracy. Ideally, these new voters will make informed decisions based on acquired knowledge and ethical considerations, free from any manipulative influences. The research methodology employed is qualitative, involving interviews and literature reviews from various journals. Qualitative methods are valuable for providing a thorough and nuanced examination of phenomena. The research findings are presented descriptively and qualitatively, with data derived from interview transcripts and articulated in narrative form rather than numerical terms. The research findings indicate that government entities, educational institutions, community organizations, and mass media play a crucial role in delivering comprehensive political education to first-time voters. This can be achieved through civic education programs, open forums for discussion, and the dissemination of accurate and readily accessible information.